Recent Development of SANS BATAN Spectrometer (SMARTer) in Serpong for Simultaneous and Automatic Measurements - E.G.R. Putra; Bharoto Bharoto; N. Suparno; Sairun Sairun; E. Santoso (PPIKSN-BATAN, 2013)
The 36 meter SANS BATAN spectrometer (SMARTer) in Serpong Indonesia has been developed for simultaneous and automatic measurements. The existing motor controller of ISA (Industry Standard Architecture) interface was replaced by the programmable motor controller of PCI (Peripheral Component Interconnect) interface, since it has speed and interrupt-sharing advantages, to drive all stepper motors for collimator, pinhole, and detector movements of the spectrometer. The recent development makes all motors moved and controlled simultaneously in setting up the instrument configuration before performing the experiment. Along with that improvement, the data acquisition software has been also developed to drive the beam stopper movement in two directions as well as to read the absolute collimator and detector positions, to acquire neutron counts on the monitor and the main detector, and also to control automatically up to 12 sample positions of the sample changer. The collected neutron counts is displayed in real time on the main monitor window, and the counts is saved in a special format for further data reduction and analysis. The developed data acquisition software has been implemented and performed for experiment that use preset time or preset count mode, and the automatic sample changer.Received: 08 November 2013; Revised: 23 December 2013; Accepted: 27 December 2013